Minat Menabung Di Bank Syariah Ditinjau Dari Literasi Keuangan Syariah,Pendapatan Dan Religiusitas - Sari, Dita Indah; Afandy, Johan (ITB AAS INDONESIA Surakarta, 2024)
This study aims to determine the effect of Sharia Financial Literacy, Income and Religiosity on in Interest saving in Islamic banks Currently there are many Islamic banks in Indonesia but most customers are more inclined to save some of their money in conventional banks than in Islamic banks which in transactions in Islamic banks are profit sharing unlike in conventional banks, namely usury which is prohibited in Islam. in this study researchers used 60 samples from 134 population. In testing researchers using SPSS 27 software tools with reliability, validity, multiple linear regression and classical assumption tests, with the results obtained, namely X1 (Islamic Financial Literacy) has a significance value of 0.030 0.05, which means that income has no significant effect on saving interest and Variable X3 (Religiousness) has a significance value of 0.000